2015
DOI: 10.19080/oajt.2015.01.555552
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Chronic Oral Nicotine Treatment in Food Consumption, Body Weight and [125I] Epibatidine Binding in Adult Mice

Abstract: Despite its abuse potential, nicotine, acting on nicotinic acetylcholine receptor, has possible medicinal uses, in particular in treating neuro degenerative diseases. Therefore, animal models to evaluate exposure need to be characterized. Administration via drinking water is a stressfree route of administration but often results in low blood nicotine levels. Here we evaluated chronic exposure to low, medium and high concentrations of nicotine in drinking water. Three-month-old C57BL/6 male mice were treated fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 58 publications
(74 reference statements)
0
3
0
Order By: Relevance
“…(2008) administered amounts varying between 50 and 200 µg/ml (5–20 mg/100 ml). The daily dose of nicotine base administered by Huang et al . (2015) was 5–55 mg/kg body weight.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…(2008) administered amounts varying between 50 and 200 µg/ml (5–20 mg/100 ml). The daily dose of nicotine base administered by Huang et al . (2015) was 5–55 mg/kg body weight.…”
Section: Resultsmentioning
confidence: 99%
“…The inability of chronic nicotine administration to enhance activity in females could be due to activity already being maximal. Other studies have also reported an anxiolytic effect of chronic nicotine administration using the OFT, but no anxiogenic effects (Cohen et al ., 2009; Huang et al ., 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation